Experimental Research for Gelator Selection in the Development of a Medicine for the Treatment of the Second Degree of Acne - Kovalenko, S. M. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this study is to develop a stable gel base with fusidic acid and to study its structural and mechanical properties. Materials and Methods: Structural and mechanical studies were conducted on a Brookfield DV-II + PRO viscometer with a rotary spindle SC4-21 (USA). The structural viscosity Å‹ (mPa â€¢ c) and the shear stress Ï„r (Pa) were measured at different shear rates of Dr or Î³ (Ñâˆ’1). With this instrument, the following parameters were measured. Colloidal stability was determined by means of a laboratory centrifuge OPN-12 of the company â€œTNK DASTANâ€ (RF). The pH value of the investigated foam samples was determined potentiometrically (DFU 1.2, 2.2.3) using the â€œpH meter Metrohm 744â€ device (Germany). Results and Discussion: The structural-mechanical and physical-chemical properties of gels with 2% fusidic acid on the basis of promising gelators were investigated, namely: Hydroxyethylcellulose, xanthan gum, sodium alginate, guar gum, and carbomer Ultrez-10 NF. Conclusions: It was proved that the best structural, mechanical, physical, and chemical consumer properties were based on a mixture of xanthan and sodium alginate. The mechanical stability indicators were calculated on the basis of structural and mechanical studies, which indicate positive extrusion properties of the selected base with fusidic acid and confirm its stability during storage (for 2 years). It was shown that a gel with fusidic acid based on a mixture of xanthan and sodium alginate represents an elastic-viscoplastic system with moderate thixotropic properties that provide the necessary extrusion and technological properties, as well as corresponding satisfactory consumer characteristics.